2005
DOI: 10.1007/s11199-005-3720-z
|View full text |Cite
|
Sign up to set email alerts
|

Players’ Gender and Male Referees’ Decisions About Aggression in French Soccer: A Preliminary Study

Abstract: The aim of this study was to examine (a) aggression displayed by players and (b) referees' decisions about these behaviors as a function of the gender of the players in French soccer. Twenty-six games (13 for women and 13 for men) were videotaped. Instrumental aggressive acts and referees' decisions were then observed. The findings indicated a significant effect of gender on instrumental aggression and referees' decisions related to these behaviors. Male players displayed more instrumental aggressive acts than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
(30 reference statements)
3
26
0
2
Order By: Relevance
“…Three studies that have included females have revealed sex differences in behavior. In a laboratory experiment, undergraduate females displayed more prosocial acts than males when playing table soccer (Sage & Kavussanu, 2007), which is a table-top game based on soccer, while in two field studies, male soccer and handball players engaged in more aggressive acts than their female counterparts (Coulomb-Cabagno & Rascle, 2006;Coulomb-Cabagno, Rascle, & Souchon, 2005). Although the two field studies recorded acts of tackling, holding back, striking, repelling, and hitting, they did not record other forms of antisocial conduct, such as provoking an opposing player or cheating.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies that have included females have revealed sex differences in behavior. In a laboratory experiment, undergraduate females displayed more prosocial acts than males when playing table soccer (Sage & Kavussanu, 2007), which is a table-top game based on soccer, while in two field studies, male soccer and handball players engaged in more aggressive acts than their female counterparts (Coulomb-Cabagno & Rascle, 2006;Coulomb-Cabagno, Rascle, & Souchon, 2005). Although the two field studies recorded acts of tackling, holding back, striking, repelling, and hitting, they did not record other forms of antisocial conduct, such as provoking an opposing player or cheating.…”
mentioning
confidence: 99%
“…We used soccer players because in this sport participants come in physical contact with the opponent during play; thus, there is high potential for moral issues to arise. We hypothesized that males would engage in less prosocial and more antisocial acts than females (see Coulomb-Cabagno et al, 2005;Sage & Kavussanu, 2007). We expected that males would be lower in empathy, perceive a lower mastery and a higher performance climate in their team, and have more soccer experience than females (Eisenberg & Lennon, 1983;Miller et al, 2005).…”
mentioning
confidence: 99%
“…In a different line of research, others have analysed the influence of the gender of team sports players on referees' decisions about transgressive game behaviours. They consistently found that although men actually displayed more aggressive behaviours than women, the latter were more penalized (Coulomb-Cabagno, Rascle, & Souchon, 2005;Souchon, Coulomb-Cabagno, Traclet, & Rascle, 2004). It is beyond the scope of this paper to explain these findings.…”
mentioning
confidence: 87%
“…Coulomb-Cabagno and Rascle (2006) contended that this difference may be due in part to social pressures relating to femininity. Pressures that were obvious in research conducted by Coulomb-Cabagno, Rascle, and Souchon (2005) who found that males use instrumental aggression more than females; yet females were punished more for their acts of aggression than males. Yet, SLT cannot adequately deconstruct how gender is related to behavior other than to suggest that female athletes learn and incorporate the social roles of athlete and woman to be used as guides for performance much the same way that one might buy and use a map.…”
Section: Post-positivist Theories Of Aggressionmentioning
confidence: 99%